Risk factors associated with changes in serum anti-Müllerian hormone levels before and after laparoscopic cystectomy for endometrioma - Zhang, Chenyu; Li, Xiaoyan; Dai, Yi; Gu, Zhiyue; Wu, Yushi; Yan, Hailan; Li, Qiutong; Shi, Jinghua; Leng, Jinhua (Frontiers in Endocrinology, 2024)
Background The objective of our study was to investigate the risk factors for a decrease in ovarian reserve in patients with endometriomas after standardized laparoscopic procedures and evaluation to provide corresponding clinical guidance for patients with fertility requirements. Methods Anti-Müllerian hormone (AMH) levels and other clinical data from 233 patients with endometriomas and 57 patients with non-endometrioma ovarian cysts admitted to the Peking Union Medical College Hospital between January 2018 and September 2023 were prospectively analysed. The pretreatment AMH levels of the study groups were compared to assess the impact of endometrioma on ovarian reserve, and the decrease in AMH after treatment was analysed to determine potential risk factors contributing to this change. Results Pretreatment AMH levels did not significantly differ between patients with endometriomas and those with non-endometrioma ovarian cysts. Within the endometrioma group, older age, higher body mass index (BMI), and shorter menstrual cycles were found to be associated with decreased AMH levels prior to treatment (p<0.05). Participants presenting with bilateral cysts, advanced surgical staging, or a completely enclosed Douglas pouch demonstrated significantly lower levels of AMH prior to treatment compared to those without these conditions (p<0.05). Furthermore, their AMH levels further declined within one year after undergoing laparoscopic cystectomy (p<0.05). However, there was no difference in AMH levels after surgery between patients who successfully became pregnant and those who did not (p>0.05). Conclusion Laparoscopic removal of endometriomas can adversely affect ovarian reserve, especially during bilateral cysts removal and when patients are diagnosed as having a higher stage of endometriosis, further impacting ovarian function. It should be noted that a decrease in AMH levels may not necessarily indicate an absolute decline in fertility. Therefore, it is crucial to conduct thorough patient evaluations and provide comprehensive patient education to offer appropriate guidance for fertility preservation.